PEMODELAN KUANTITATIF DETERMINAN-DETERMINAN YANG MEMPENGARUHI KEMATIAN PERINATAL - Sri rejeki, Dwi Sarwani; Aji, Budi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2008)
Martenal Mortality Rate (MMR) and Perinatal Death Rate (PFR) were indicators to measure performance of antenatal carte for all countries.  Every year about eight million perinatal death rates or die in the first month of delifery. Perinatal Death Rate (PFR) in Banyumas Regency was 2,96/100 or 62 cases in 2005. High Perinatal Death Rate in Banyumas Regebcy caused researched interested to identify causal factors related PDR. Quantitative modeling to analyze causal factors of perinatal Death Rate. The study observational research with case control design approach, there were 58cases and 58 sampling. As case group was all PDR in BAnyumas Regency and control groupwas all survive baby borne in the same block (1RT) and the same brith day with case group. There are some significantly effect toward perinatal death rate, asphyxia (OR=93,13 95% CI=12,06 ? 917,31); Low income (OR = 76,70 95% CI=4,56 ? 1289,08 ; Infection ((OR=46,06 95% C1=3,64 ? 582,68) ; and lowbirth weight (OR 7,55 95% C1 =1,71 ? 33, 25). Quantitative model  as following Y             = 1 1+ e ?(constans + B asphyxia + B infection+B low birth  weight Continuum antenatal care and seeking for health treatment if there are any co morbiduity with the baby such as asphyxia , infectuoinn an low birth weight.